HUBUNGAN HIGIENE SANITASI DENGAN KUALITAS MIKROBOLOGIS PADA MINUMAN ES THAI TEA DI KECAMATAN TEMBALANG - Nurtiyana Mawarni; Retno Hestiningsih; Nissa Kusariana; M. Arie Wuryanto (Jurnal Kesehatan Masyarakat (Undip), 2019)
This time, tea has been modified to kinds of drinks, one of them was ice Thai Tea. Based on the components and process of Thai Tea making is very possible occurrence of bacterial and fungal contamination. The purpose of this research is to analyze relations between hygiene sanitation with microbiological quality in ice Thai Tea in Tembalang. This study is observational-analytic with using cross sectional design. The samples were 31 samples of ice Thai Tea. Data were analyzed using Fisher Exact. The results showed that most of ice Thai Tea did not quality with 26 samples (83,9%) of unqualitified Coliform status, 21 samples (67,7%) were contaminated with Escherichia coli, and 5 samples (16,1%) were contaminated with yeast/ mold/ fungi. This study shows there is relations between personal hygiene (p=0,043) and sanitation equipment (p=0,043) with microbiological quality in ice Thai Tea but there is not relations between storage of raw materials (p=0,058) and sanitation place (p=0,631) with microbiological quality in ice Thai Tea. Traders should pay attention to personal hygiene and sanitation equipment when making ice Thai Tea so that bacterial contamination can be minimized.